Manometric evaluation of anorectal function in patients treated with neoadjuvant chemoradiotherapy and total mesorectal excision for rectal cancer - De Nardi, Paola; Testoni, Sabrina Gloria Giulia; Corsetti, Maura; Andreoletti, Hulda; Giollo, Patrizia; Passarett, Sandro; Testoni, Pier Alberto (Springer, 2017)
BACKGROUND: An altered anorectal function is reported after chemoradiotherapy (CRT) and surgery for rectal cancer. AIM: The aim of this study was to clarify the relative contribution of neoadjuvant chemoradiation and surgical resection on the impairment of anorectal function as evaluated by anorectal manometry. METHODS: Thirty-nine patients with rectal cancer, who underwent neoadjuvant CRT and laparoscopic rectal resection, were evaluated with the Pescatori Faecal Incontinence score, and with anorectal manometry: before neoadjuvant therapy (T0), after neoadjuvant therapy and before surgery (T1), 12 months after stoma closure (T2). RESULTS: Resting and/or maximum squeeze pressure and/or volume thresholds for urgency were below the normal values in 12 (30%) patients at baseline. After CRT the mean resting pressure significantly decreased (p=0.007). Surgery determined a significantly decrease of the resting pressure (p=0.001), of the maximum squeeze pressure (p=0.001) and of the volume threshold for urgency (p=0.001). Impairment of continence was reported by 5, 11 and 18 patients at T0, T1 and T2, with a mean incontinence score of 3, 3.8 and 3.9 respectively. CONCLUSIONS: CRT is detrimental to the function of the internal anal sphincter. Rectal resection significantly affects both internal and external anal sphincter function and the maximum tolerated volume of the neo-rectum, particularly in patients with low rectal cancer, significantly impairing anal continence.